SISTEM PENDUKUNG KEPUTUSAN PENDUGAAN UMUR SIMPAN & TANGGAL KADALUARSA PRODUK PANGAN DENGAN METODE ARRHENIUS BERBASIS WEB - Irfianti, Asti Dwi; STP, MP, Rosida (REKAPANGAN, 2010)
The concept of Decision Support Systems is one branch of artificial intelligence which is widely used.  There  are  many  methods  that  can  be  used  by  decision  makers  to  find  the  optimum solution or alternative to a problem. One such method is the method of Arrhenius. This method will  help  decision  makers  where  many  alternative  decisions  with  multiple  criteria.  This research will apply prediction shelf life and expiration dates with three different temperatures. At  this  time  in  the  counting  process  prediction  shelf  life  expiration  date  carried  out  by conventional  means  which  are  found  to  be  inefficient,  with  the  Arrhenius  method pangaplikasian  writer trying  to  create  an  auxiliary  system  for  processing  plant  food  products to determine shelf life and expiration date. The input data research, the raw data is processed into a desired output based on the parameters taken. The methodology is the identification of system requirements with system modeling, analysis, information needs of data storage with a conceptual data model and physical data models as the material content of the material system. Test  the  feasibility  of  web-based  Decision  System  is  done  by  performing  a  series  of  test scenarios  include:  test  parameters,  product  testing,  trials  of  sub  products,  organoleptic  test data (research data).Keywords: shelf life, organoleptic data, Artificial Intelligence, Decision Support System